POLA PEMBENTUKAN KELOMPOK TANI (Studi di Kabupaten Malang) - Pratama, Yogi Pasca; Samudro, Bhimo Rizky (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2018)
This study aims to determine the pattern formation of farmer groups and the dynamics surrounding it. Theoretically, this research is expected to complement previous studies and as a material for further study the interaction problems of farmers in the group. The research method in this study is a qualitative descriptive symbolic interaction perspective. The unit of analysis in this study is the interaction between individuals in a partnership contract with the farmers do Perhutani office and perceptions that arise from the current fertility involved in these interactions. The data collection is done by means of unstructured interviews, in-depth interviews (depth interview), and the observation participation. The data were analyzed qualitatively. The study's findings include the discovery of the three main sources of formation of farmer groups, which are formed due to the dynamics problem fertilizer distribution mechanism, their help, and through association study.Ultimately verifier will recommend the farmer group based institutional track record and activeness in the sustainability of the program, both in terms of activities, maintenance, as well as the accountability side.